Approximation by Generalized Faber Series in Weighted Bergman Spaces on Infinite Domains With a Quasiconformal Boundary - Israfilov, Daniyal M.; Yildirir, Yunus E. (Sarajevo Journal of Mathematics, 2024)
Using an integral representation on infinite domains with a quasiconformal boundary the generalized Faber series for the functions in the weighted Bergman space A^2(G,ω ) are defined and its approximation properties are investigated. 2000 Mathematics Subject Classification. 30E10, 41A10, 41A25, 41A58